John Haught on original sin: A conversation - Conradie, Ernst M. (HTS teologiese studies, 2016)
This article engages with John Haught’s views on original sin. It offers a brief orientation todiscourse on sin in the context of theological debates on human evolution. This is followed bya thick description of Haught’s so-called note on original sin. A series of five observations andquestions regarding Haught’s position is offered. It is observed that Haught’s way of tellingthe story of sin and salvation follows a classic Roman Catholic plot, namely one based on graceelevating nature. This is contrasted with the more typically reformed plot of restoration.